Evaluation and Comparison with Other High-Sensitivity Methods of Analytical Performance and Measured Values of a New Laboratory Test for Cardiac Troponin I Assay. (8th April 2021) - Masotti, Silvia; Musetti, Veronica; Prontera, Concetta; Storti, Simona; Passino, Claudio; Clerico, Aldo
Abstract: Bakground: The aim of this study was to evaluate both analytical characteristics and clinical results of a new chemiluminescent method for the measurement of cardiac troponin I (cTnI), named VITROS ® High Sensitivity Troponin I Assay, using the VITROS ® 3600 automated platform. The results found with this new method were compared to those observed with hs-cTnI ARCHITECT and ECLIA hs-cTnT ELECSYS methods. Methods: For evaluation of analytical performance and comparison of clinical results, plasma samples (lithium-heparin), were collected from apparently healthy subjects and patients with cardiovascular diseases. Results: The hs-cTnI VITROS method showed values for limit of blank (LoB 0.33 ng/L), limit of detection (LoD, 0.91 ng/L), limit of quantifications at 20% (LoQ 20% CV, 1.82 ng/L), and 10% (LoQ 10% CV, 4, 74 ng/L), which are comparable to those previously reported for other hs-cTnI methods. Moreover, the clinical results of the hs-cTnI VITROS method were found to be closely correlated to those of hs-cTnI ARCHITECT (R = 0, 9883, N = 198) and ECLIA hs-cTnT Elecsys (R = 0, 9704, N = 293) methods. Conclusions: The hs-cTnI VITROS method shows analytical performance comparable to other cTnI and cTnT assay. The results of this study confirm that there are significant systematic differences among hs-cTnI methods. Further multicenter studies using larger reference populations are needed in order to obtain a better estimation, especially of the 99° percentile URL values categorized for sex and age of hs-cTnI and hs-cTnT methods.